Dental data challenge the ubiquitous presence of Homo in the Cradle of Humankind - (:unkn) unknown (My University, 2022)
The origins of Homo , as well as the diversity and biogeographic distribution of early Homo species, remain critical outstanding issues in paleoanthropology. Debates about the recognition of early Homo , first appearance dates, and taxonomic diversity within Homo are particularly important for determining the role that southern African taxa may have played in the origins of the genus. The correct identification of Homo remains also has implications for reconstructing phylogenetic relationships between species of Australopithecus and Paranthropus , and the links between early Homo species and Homo erectus . We use microcomputed tomography and landmark-free deformation-based three-dimensional geometric morphometrics to extract taxonomically informative data from the internal structure of postcanine teeth attributed to Early Pleistocene Homo in the southern African hominin-bearing sites of Sterkfontein, Swartkrans, Drimolen, and Kromdraai B. Our results indicate that, from our sample of 23 specimens, only 4 are unambiguously attributed to Homo , 3 of them coming from Swartkrans member 1 (SK 27, SK 847, and SKX 21204) and 1 from Sterkfontein (Sts 9). Three other specimens from Sterkfontein (StW 80 and 81, SE 1508, and StW 669) approximate the Homo condition in terms of overall enamel–dentine junction shape, but retain Australopithecus -like dental traits, and their generic status remains unclear. The other specimens, including SK 15, present a dominant australopith dental signature. In light of these results, previous dietary and ecological interpretations can be reevaluated, showing that the geochemical signal of one tooth from Kromdraai (KB 5223) and two from Swartkrans (SK 96 and SKX 268) is consistent with that of australopiths.
Keywords: African Research